Caregiver outcomes and interventions: a systematic scoping review of the traumatic brain injury and spinal cord injury literature. (January 2017) - Baker, Anne; Barker, Samantha; Sampson, Amanda; Martin, Clarissa
Aim: To identify factors reported with negative and positive outcomes for caregivers of the traumatic brain injury and spinal cord injury cohorts, to investigate what interventions have been studied to support carers and to report what effectiveness has been found. Methods: Scoping systematic review. Electronic databases and websites were searched from 1990 to December 2015. Studies were agreed for inclusion using pre-defined criteria. Relevant information from included studies was extracted and quality assessment was completed. Data were synthesised using qualitative methods. Results: A total of 62 studies reported caregiver outcomes for the traumatic brain injury cohort; 51 reported negative outcomes and 11 reported positive outcomes. For the spinal cord injury cohort, 18 studies reported caregiver outcomes; 15 reported negative outcomes and three reported positive outcomes. Burden of care was over-represented in the literature for both cohorts, with few studies looking at factors associated with positive outcomes. Good family functioning, coping skills and social support were reported to mediate caregiver burden and promote positive outcomes. A total of 21 studies further described interventions to support traumatic brain injury caregivers and four described interventions to support spinal cord injury caregivers, with emerging evidence for the effectiveness of problem-solving training. Further research is required to explore the effects of injury severity of the care recipient, as well as caregiver age, on the outcome of the interventions. Conclusion: Most studies reported negative outcomes, suggesting that barriers to caregiving have been established, but not facilitators. The interventions described to support carers are limited and require further testing to confirm their effectiveness.